Student motivation in a real investment decision making case study - Plaza-Casado, Paola; Escamilla-Solano, Sandra; Orden-Cruz, Carmen (Journal of Management and Business Education, 2020)
One of the main concerns of the university is the ability to respond to the training needs of future workers. The disconnection between the theory and the practise causes demotivation because sometimes knowledge learned in the classroom has no direct application at work. The purpose of this study is to evaluate student motivation through investment decision-making real case using gamification techniques and an incentive system. The results showed a positive impact since students improved their learning and appreciated its usefulness. The main conclusion is the necessity to include real examples in the classroom.